Gates, Hired Guns and Mistrust - Business Unusual : The Cost of Crime and Violence to Businesses in Papua New Guinea - Lakhani, Sadaf (World Bank, Washington, DC, 2014)
High levels of crime and violence are widely viewed as a critical constraint to development in Papua New Guinea (PNG). The most casual discussion on the topic inevitably elicits stories of personal experiences of victimization, or those of friends or family. Reports of violent incidents appear in the media on a daily basis. Despite 10 years of strong economic growth, with an increase in GDP of over 8 percent in 2011, there is a perception is that crime and violence have an impact on the business climate in the country, and that the costs to development are significant. This paper is the fourth in a series produced by the World Bank as part of the study "Socioeconomic Costs of Crime and Violence in PNG". The aim of the study has been to conduct targeted data collection and mine existing information sources, creating new analyses, in order to feed an informed dialogue among key stakeholders in PNG, and to help the business community in their ongoing discussions. As such, the study provides an overview of costs according to key themes along with presenting relevant empirical evidence, rather than a detailed accounting.